Informing conservation of African-Eurasian migratory landbirds, raptors and storks using tracking data. - (:unkn) unknown (My University, 2022)
African-Eurasian migratory landbirds, raptors and storks face a suite of anthropogenic threats across their ranges and, as a result, many populations of these species are declining and need urgent conservation. However, the conservation of these birds is challenging, requiring the cooperation of all countries linked by their movements and a sound understanding of their spatial and temporal distributions across the annual cycle. In this thesis, I took a multispecies approach, and compiled and synthesized information from existing data of birds tracked along the flyway for establishing baselines to inform international conservation efforts. More specifically, my objectives were to better understand the spatial and temporal distributions of African-Eurasian migratory landbirds, raptors and storks during the non-breeding season, investigate their connectivity patterns between the breeding and non-breeding grounds, and identify priorities for future research, conservation action and international cooperation. In Chapter 1, I reviewed the tracking literature to synthesize current knowledge on the connectivity established between countries by African-Eurasian migratory landbirds and raptors. Then, I identify the main knowledge gaps and suggest priorities for future tracking efforts, and highlight important cooperation opportunities based on shared conservation priorities among countries. In Chapter 2, I compiled existing tracking data from an extensive network of collaborators to build a new tracking dataset of African-Eurasian migratory landbirds, raptors, and storks, as a basis for analyses to inform international conservation. All data was standardized to make them comparable and tracks classified into phenological periods. In Chapter 3, I combined the tracking data compiled in Chapter 2 with data on population size, and developed a multi-species indicator to map the relative importance of different areas, ecoregions and countries for African-Eurasian migr
Keywords: African Research